Effect of Chlorhexidine and Povidone-iodine Mouth Rinses on Corrosion Resistance and Surface Characteristics of Stainless Steel Orthodontic Brackets – An in vitro and in vivo Study - Ragul Pugalendhi; N. K. Sapna Varma; Parvathy Ghosh; V. V. Ajith; Deepika Jayakrishnan Nair (Contemporary Clinical Dentistry, 2024)
Background: Stainless steel (SS) orthodontic brackets may have varying corrosion resistance when used with mouthwashes during orthodontic treatment. Studying their effects on orthodontic brackets will be beneficial. Aim: The study’s objective was to analyze the surface characteristics of SS orthodontic brackets and their resistance to corrosion, exposed to chlorhexidine and povidone-iodine mouth rinses – an in vitro and in vivo study. Materials and Methods: The in vitro test: MBT 0.022” slot SS orthodontic brackets were immersed in three groups – Group A – Modified Meyer-Fusayama artificial saliva (AS), Group B – Chlorhexidine, and Group C – Povidone-iodine mouthwash. The in vivo test: Brackets were conventionally bonded on the patient’s teeth and divided into Group I – control group, Group II – patients used chlorhexidine, and Group III used povidone-iodine mouth rinse. The corrosion resistance and surface characteristics of SS brackets were determined using scanning electron microscope (SEM), electrochemical impedance spectroscopy, and X-ray photoelectron spectroscopy. Results: Higher corrosion resistance was obtained for brackets immersed in chlorhexidine mouth rinse. The polarization resistance value of the orthodontic SS bracket was 109 MΩ, 1383 MΩ, and 769 MΩ immersed in AS, chlorhexidine, and povidone-iodine mouth rinse, respectively. After surface chemical analysis, XPS data showed the largest intensity peak of metallic chromium (CrO) fresh sample and in the sample immersed in chlorhexidine mouthwash. According to SEM, brackets immersed in chlorhexidine showed a relatively smooth surface. Conclusion: In this study, chlorhexidine was found to be less corrosive followed by povidone-iodine.